ANALISIS EFEKTIVITAS PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI INFORMASI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Ridwan Ali (LPPM Universitas Cipta Mandiri, 2025)
This study aims to analyze the effectiveness of using information technology (IT)-based learning media in the teaching and learning process of Islamic Religious Education (PAI). In the digital era, characterized by rapid technological advancement, teachers are required to adapt to more interactive teaching approaches that align with the characteristics of Generation Z and Alpha. Through a literature review of previous studies, it was found that IT-based media such as e-learning, interactive videos, mobile applications, and online learning platforms are capable of increasing learning motivation, students’ active participation, as well as their understanding of the abstract and conceptual materials in PAI. Nevertheless, the implementation of IT media is not without challenges, such as limited infrastructure, low digital competence among teachers, and the lack of digital PAI materials that are aligned with the curriculum. Critical analysis indicates that the effectiveness of IT media largely depends on the readiness of educational institutions, the quality of digital content, and the pedagogical strategies employed by teachers. Therefore, synergy is needed between technological development, the improvement of educators’ competencies, and the provision of contextual learning resources so that IT media can truly become an effective tool in PAI learning.